Modern nature Alberto Baraya, Mark Dion, Simryn Gill, Derek Jarman, Hilma af Klint, Margaret Mee, Christine Ödlung, David Thorpe, Viktor Timofeev - MacFarlane, Kate; Stout, Katharine ca. 20./21.Jh (Drawing Room, 2019)
Modern Nature explores our interaction and fascination with plants in relation to aspects of social change, personal well-being and scientific research. The exhibition brings together drawings never before exhibited in the UK by historical artists Hilma af Klint and Margaret Mee, alongside works by contemporary international artists, including pseudo-botanist Alberto Baraya and explorer, activist and artist Mark Dion, to explore utopian ideas of the redeeming qualities of nature and the contradictory reality that plastic waste and over-farming are damaging the natural world. Also included are unique works on paper by Simryn Gill and Christine Ödlund, diary entries by filmmaker, diarist and gardener Derek Jarman, anthropomorphised botanical watercolours by David Thorpe and an exuberant newly commissioned wall drawing by Viktor Timofeev, which together consider the notion of care in relation to man's interdependency with plant life
In Papiertüte. - Haupttitel vom Behältnis
Published in 2019 by Drawing Room in an edition of 300 on the occasion of the exhibition "Modern Nature", 2 May - 7 July 2019, Drawing Room, London
Includes bibliographical references
Keywords: Mee, Margaret -- 1909-1988; Ödlund, Christine -- 1963-; Dion, Mark -- 1961-; Klint, Hilma af -- 1862-1944; Gill, Simryn -- 1959-; Baraya, Alberto -- 1968-; Jarman, Derek -- 1942-1994; Thorpe, David -- 1972-; Timofeev, Viktor -- 1984-; Pflanzendarstellung; Ausstellungskatalog -- Drawing Room -- 02.05.2019-07.07.2019 -- London; Bildband